Perancangan Aplikasi Database Sistem Pengelolahan Arsip Digital Berbasis Web Mobile Menggunakan Algoritma Levensthein (Studi Kasus : SMA PLUS TARUNA AKTERLIS MEDAN) - Rizky ananda fradana; Leni Marlina (CV. Hawari, 2025)
Archive management that is still done manually at SMA Plus Taruna Akterlis Medan often causes difficulties in searching and archiving documents efficiently. Therefore, this study aims to design and build a web-based mobile digital archive management system using the Levenshtein Algorithm to improve document search efficiency. This system was developed using the PHP programming language and MySQL database, and implementing object-based system analysis modeling, such as Use Case Diagrams, Class Diagrams, and Activity Diagrams. The Levenshtein Algorithm is used in this system to improve the accuracy of document searches based on the similarity of keywords entered by the user, thus facilitating the archive search process. The prototype system developed allows users to manage archive data digitally, including recording incoming and outgoing letters. The implementation of this system is expected to increase the effectiveness and efficiency of archive management in the school environment.